Proteoglycans and Immunobiology of Cancer—Therapeutic Implications - Tzanakakis, George; Neagu, Monica; Tsatsakis, Aristidis; Nikitovic, Dragana (Frontiers in Immunology, 2019)
Disparity during the resolution of inflammation is intimately associated with the initiation and progression of the tumorigenesis. The transformed cells, through continuously evolving interactions, participate in various exchanges with the surrounding microenvironment consisting of extracellular matrix (ECM) components, cytokines embedded in the ECM as well as the stromal cells. Proteoglycans (PGs), complex molecules consisting of a protein core into which one or more glycosaminoglycan (GAG) chains are covalently tethered, are important regulators of the cell/matrix interface and consecutively biological functions. Discrete expression of PGs and their interacting partners has been distinguished as specific for disease development in diverse cancer types. In this mini-review we will comprehensively discuss the roles of PGs in the complex processes of cancer associated modulation of the immune response and analyze their mechanisms of action. Deeper understanding of mechanisms which are capable of regulating the immune response could be harnessed to treat malignant disease.